Ukrainian-Romanian Relations at the Background of Russia’s Revisionist Policy - Zlatin, О. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2017)
The purpose of this article is to analyse relations between Ukraine and
Romania in the post-communist period. It provides a deep insight into the
evolution of these relations in the context of Russia’s aggression against
Ukraine. The study gives a general overview of the bilateral relations between the
two neighbouring countries since the collapse of USSR and restoration of
Ukraine’s independence in 1991, focusing on a wide range of irritants both
great and small. Further, the research highlights turbulent relations between Kyiv and
Bucharest from the historical and socio-cultural perspective.
Another neuralgic issue analysed in this paper is Russian illegal
annexation of the Crimea and its aggression against Ukraine, which not only
destabilised the security balance in the Black Sea, Eastern Mediterranean and
Middle East by establishing a large anti-access/area-denial exclusion zone but
also caused the greatest threat to the national security of Romania. In fact,
with Russia being its direct maritime neighbour Romania cannot cope with this
threat alone. Furthermore, the study shows that Russian aggression against Ukraine
resulted in intensifying rapprochement between Ukraine and Romania since
2014. Subsequently, Romania condemned the Kremlin’s aggression and
became one of the Ukraine’s advocates within the international organisations
like the EU, NATO, and the UN. Finally, it is also noteworthy that summit meetings between Kyiv and
Bucharest reveal the new phase in their bilateral relations based on the “security first” approach. Стаття присвячена дослідженню відносин між Україною й Румунією
в пост-комуністичний період. Здійснюється аналіз еволюції цих взаємин у
контексті агресії Росії проти України.
Подається узагальнюючий огляд двосторонніх відносин між сусідніми країнами починаючи з розпаду СРСР і відновлення незалежності
України в 1991 році з акцентом на широкому спектрі проблемних питань.
У статті висвітлюються контроверсійні взаємини між Києвом та
Бухарестом з історичного та соціокультурного поглядів.
Іншим важливим питанням, що аналізується, є незаконна окупація
Криму Росією та її агресія проти України, внаслідок якої не лише порушено баланс сил у регіонах Чорного, Середземного морів і Близького Сходу, а й зросла загроза національній безпеці Румунії. По суті, маючи Росію
своїм прямим морським сусідом, Румунія не може впоратись із цією
загрозою самотужки. Більше того, дослідження показує, що агресія Росії проти України
призвела до зближення між Україною й Румунією починаючи з 2014 року.
Румунія засудила агресію Кремля й стала одним із адвокатів України в
міжнародних організаціях, зокрема в ЄС, НАТО та ООН. Також слід відзначити, що зустрічі на найвищому рівні між Києвом і
Бухарестом розкривають новий етап двосторонніх відносин на основі підходу «безпека насамперед».